2016
DOI: 10.9787/pbb.2016.4.3.373
|View full text |Cite
|
Sign up to set email alerts
|

A Quick and Simple In-house Screening Protocol for Cold-Tolerance at Seedling Stage in Rice

Abstract: This is an Open-Access article distributed under the terms of the Creative Commons Attribution Non-Commercial License (http://creativecommons.org/licenses/by-nc/4.0) which permits unrestricted non-commercial use, distribution, and reproduction in any medium, provided the original work is properly cited. ABSTRACT Cold stress is an emerging threat for rice production in Bangladesh particularly in Boro season (winter rice) at seedling stage. Cold stress during seedbed stage or early establishment stage at the mai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 13 publications
0
8
0
Order By: Relevance
“…LD score, % survivability and % recovery (Table 2). Khatun, et al [9] also reported cold sensitivity of these two varieties. Among the five genotypes tested for seedling stage cold tolerance, BR18 and Hbj.BVI showed moderate to high tolerance to cold stress at seedling stage, respectively.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…LD score, % survivability and % recovery (Table 2). Khatun, et al [9] also reported cold sensitivity of these two varieties. Among the five genotypes tested for seedling stage cold tolerance, BR18 and Hbj.BVI showed moderate to high tolerance to cold stress at seedling stage, respectively.…”
Section: Discussionmentioning
confidence: 92%
“…Among the eight cultivars, BR1, BR18, BRRI dhan28, BRRI dhan29 and Hbj.B.VI were evaluated against artificial cold treatment for seedling stage cold tolerance following protocol described in Khatun, et al [9]. Cold tolerance was estimated based on leaf discoloration (LD) score following SES of IRRI, % Survival plants at day of scoring and % Recovery of plants after seven days of cold stress withdrawal.…”
Section: Methodsmentioning
confidence: 99%
“…Some studies used constant temperature varying from 4 to 12°C (Zhan et al 2005;Andaya and Mackill 2003;Qu et al 2003;Han et al 2005a, b) and some others used variable temperature over day to night (20/13°C by Park et al 2013, 10/6°C by Qian et al 2000. Khatun et al (2016) reported that cold water irrigation with constant 13°C in cold water tank at 3-leaf stage-seedlings of rice for 7 days is sufficiently enough to discriminate cold tolerant varieties from intolerant ones, and it is as good as constant 10°C treatment. Yoshida (1981) reported 10°C as the minimum critical value, below which rice seedlings get yellowing and stunted growth and loses potency to survive (Yoshida 1981).…”
Section: Discussionmentioning
confidence: 99%
“…Parents, check varieties, and F 2:3 progenies were evaluated under artificial cold stress condition using cold water irrigation in cold water tank in 2014 following the protocol described in Khatun et al (2016) with slight modification. Briefly, 30 seedlings of each of parents, check varieties, and F 3 families were raised in plastic trays filled with gravel free fertilized soil.…”
Section: Evaluation Of Cold Tolerance At Seedling Stagementioning
confidence: 99%
“…LTS causes loss of rice yields in several ways [17]. LTS during germination causes seedling death and delayed crop establishment [18], whereas during the vegetative stage, LTS reduces rice yield by reducing rice biomass [15]. LTS during jointing reduces grain yield by decreasing the number of spikelet per panicle [19].…”
Section: Introductionmentioning
confidence: 99%